2017
DOI: 10.1142/s1363919617400102
|View full text |Cite
|
Sign up to set email alerts
|

Innovators and Early Adopters in the Diffusion of Innovations: A Literature Review

Abstract: Despite accounting for a very small percentage of the population that adopts an innovation, the ‘innovators’ and ‘early adopters’ — representing the two earliest groups of individuals to acquire the new product or service — play a crucial role in the dissemination of the innovation to larger market segments. The objective of this paper is to understand the characteristics of these individuals that positively influence their decisions to adopt innovations. We argue that awareness of these traits will enable fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 65 publications
6
44
0
2
Order By: Relevance
“…Most researchers focused on the discussions of innovation influences [10][11][12][13][14][15], innovation diffusion [16][17][18][19] and the characteristics and behaviors, as well as the relationship between these two, among early adopters [20,21]. Dedehayir et al [22] suggested that understanding the consumers' willingness and unwillingness to adopt innovations were equally important. Exploring the reasons for consumers' unwillingness to adopt innovations could not only help enterprises develop more smoothly in the initial stages, but also further modify the innovations, so as to meet the genuine requirements of consumers who did not adopt the innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers focused on the discussions of innovation influences [10][11][12][13][14][15], innovation diffusion [16][17][18][19] and the characteristics and behaviors, as well as the relationship between these two, among early adopters [20,21]. Dedehayir et al [22] suggested that understanding the consumers' willingness and unwillingness to adopt innovations were equally important. Exploring the reasons for consumers' unwillingness to adopt innovations could not only help enterprises develop more smoothly in the initial stages, but also further modify the innovations, so as to meet the genuine requirements of consumers who did not adopt the innovations.…”
Section: Introductionmentioning
confidence: 99%
“…When appraising their work (reflexive monitoring), most success was seen when pharmacists took it upon themselves to effect change; when this occurred, there was real potential for this to overcome the barriers to implementation and to achieve and maintain normalization. It could be that pharmacists who had been proactive, had positive attitudes to innovation or were, ‘early adopters’ [53]. Others have described these pharmacists as engaging fully with training and learning activities, being receptive to innovative behaviours and welcoming greater autonomy [54].…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the early majority, the late majority consists of individuals who are initially highly sceptical of innovation and will consider OS practices only after a critical mass of peers have adopted them (Rogers, 2003) . Compared to the late majority, the early majority is more likely to form positive perceptions of innovation and can be more receptive to change (Dedehayir et al, 2017) . Encouraging adoption of OS by the early majority can facilitate a paradigm shift in research practices, and is therefore the needed step to engage the late majority in adopting OS practices.…”
Section: Open Science Communitiesmentioning
confidence: 99%